CLINICAL AND PATHOGENETIC FEATURES OF COMMUNITY-BASED INFECTION AND MICRONUTRITIVE STATUS AMONG CHILDREN (Multidisciplinary Journal of Science and Technology, 2025)
Community-based infection (CIP) is one of the main causes of infectious diseases among children, with high mortality and morbidity rates globally. This article is devoted to an in-depth study of the clinical signs, pathogenetic mechanisms of CIP in children, and the impact of micronutrient deficiencies on this disease. The article reviews the impact of micronutrient deficiencies, in particular, vitamin D, zinc, selenium, vitamin A, and iron deficiencies on the immune system, disease severity, protracted course, risk of recurrence, and treatment outcomes. The diversity of pathogens (Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus, Mycoplasma pneumoniae, respiratory syncytial virus), their resistance to antibiotics, virulence factors, and age-specific characteristics of the disease in children are also analyzed. Based on studies conducted in Uzbekistan, the prevalence of chronic forms of SLE is 10.8-11.3%, the role of perinatal risk factors (anemia, acute respiratory infections of the mother during pregnancy), underlying diseases (asthma, allergies), and environmental factors is emphasized. The impact of micronutrient deficiencies on the course of the disease is shown, for example, vitamin D deficiency in 53.1% of cases, a 2.6-3.0-fold decrease in zinc and selenium levels, as well as an increase in the risk of infection with vitamin A and iron deficiency. The study emphasizes the importance of a comprehensive approach to the treatment and prevention of SLE, including antibiotics, micronutrient supplementation (zinc 10-20 mg/day, vitamin D 1000-2000 IU/day, vitamin A) and immunomodulators. The article is based on the scientific literature and aims to analyze current data, present personalized methods of diagnosis and treatment, which will help reduce the burden of SLE in children. The role of micronutrient deficiencies and the importance of vaccination during the COVID-19 pandemic are also reviewed.